Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Pegawai pada Kecamatan Pagedangan - Dewi Lestari; Ana Septia Rahman; Santi Octavianti; Hafis Laksmana Nuraldy (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Employee performance is an important factor in achieving organizational goals, particularly in public sector institutions that demand effective and efficient public services. Motivation and work discipline are considered essential aspects that can influence employee performance improvement. However, several organizational problems such as low work motivation, lack of discipline, absenteeism, and work delays may negatively affect employee productivity and organizational effectiveness. Therefore, this study aims to analyze the influence of motivation and work discipline on employee performance at the Pagedangan District Office, Tangerang. This study employed a quantitative research approach using a survey method. The respondents consisted of 90 employees selected using a census sampling technique. The research data were collected through the distribution of questionnaires using a Likert scale. The collected data were processed using SPSS version 27 and analyzed through multiple linear regression analysis. The results of the study indicate that motivation has a positive and significant effect on employee performance. Work discipline also has a positive and significant influence on employee performance. Simultaneously, motivation and work discipline significantly affect employee performance and contribute substantially to improving work effectiveness and organizational productivity. These findings demonstrate that strengthening employee motivation and maintaining work discipline are important strategies for improving employee performance in public organizations.